BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2012)
Plant Bacteriology by Dr. Kalyan K. Mondal (ISBN: 978-93-272-1631-8), Kalyani Publishers, Lyall Book Depot, 2011, pp. 190, Price Rs. 225/- The book entitled â€œPlant Bacteriologyâ€ by Dr. Kalyan K. Mondal, Senior Scientist, Plant Bacteriology Section, Division of Plant Pathology, Indian Agricultural Research Institute (IARI), New Delhi and published by Kalyani Publishers is a welcome attempt in the discipline of teaching plant pathology in India. As claimed by the author, the content of the book has been designed keeping in mind syllabi of introductory plant bacteriology course being followed in Indian Agricultural Research Institute and State Agricultural Universities in India. The book has succeeded reasonably well as an effective primer for the ever-expanding field of bacteriology in general and plant bacteriology in particular.